Duckweed (Lemna minor) in Feed to Increase the Carcass and Giblet Proportion of Male Alabio Ducks - Herliani; Danang Biyatmoko; Abrani Sulaiman; Habibah; Puteri Amilia (Postgraduate, University of Mataram, 2025)
Feeding containing wet duckweed increases the feed conversion ratio. This research aims to analyze the effect of differences in the use of wet duckweed and duckweed flour in rations on the percentage of carcass and giblet cuts of male Alabio ducks. This research was carried out in the Experimental Cages of the Faculty of Agriculture, Lambung Mangkurat University using 108 Alabio ducks. The study used three treatments, namely P0 (control, without duckweed), P1 (20% wet duckweed in the ration), and P2 (20% duckweed flour in the ration). The parameters observed included the percentage of chest, thigh, back, wing and giblet weight to carcass weight. Duckweed with complete feed has the same results so it can be used as a substitute feed and between the two treatments P1 and P2 it is known that the use of wet duckweed gives the best percentage of carcass cuts.